Phytochemical screening and Antioxidant activity of Cananga odorata extract - Chew, Khe Jiea; Fuloria, Shivkanya; Vetriselvan, Subramaniyan; Mahendran, Sekar; Kathiresan, V Sathasivam; Saminathan, Kayarohanam; Wu, Yuan Seng *; Venkata Sathya, Saiappala Raju Velaga; Ashok Kumar, Janakiraman; Mohammad Nazmul, Hasan Mazia; Fuloria, Neeraj Kumar (Research Journal of Pharmacy and Technology, 2022)
Plants are the natural source for the antioxidants from plants source is boon for the investigators. Present study was aimed to study the antioxidant activity and phytochemical screening of Cananga odorata (Lam.) Hook. f. & Thomson extract. Study involved preparation hydroalcoholic extract of Cananga odorata leaves (HECOL) using maceration method, followed by its phytochemical screening and antioxidant activity. The HECOL was subjected to determination of total phenolic content (TPC) and total flavonoid content (TFC), and DPPH (1,1-Diphenyl-2-picryl hydrazyl) radical scavenging assay for determination of antioxidant activity. Maceration of C. odorata using hydroalcoholic solvent offered dark brown colored HECOL. Phytochemical screening of HECOL exhibited presence of carbohydrates, mucilage, fats and oils, volatile oils, anthraquinone glycosides, flavonoids, alkaloids, tannins and phenolic compounds. For TPC the gallic acid equivalent of HECOL was found to be 0.507 mg GAE/g. Whereas for TFC, the rutin equivalent of HECOL was found to be 0.2224mg RE/g. The antioxidant activity of HECOL was estimated to be 120.44μg/ml (IC50). Based on the experimental results, present study concludes that HECOL possess the significant antioxidant potential. This study also recommends that antioxidant activity potential of C. odorata leaves should be further explored using different solvent extracts.